Initial Results of Research into Brown Bear Timber Damage (Ursus arctos) in Silver Fir (Abies alba) Forests in Croatia - Krešimir Krapinec; Dario Majnarić; Davor Jovanović; Igor Kovač; Ivica Medarić (Croatian Journal of Forest Engineering, 2011)
The paper analyzes the inventories of trees debarked by the brown bear. Sample plots were established in mixed beech-fir forests in the mountainous part of western Croatia (an area in which such type of damage is relatively frequent). The method of damaging trees is similar to that incurred by the black bear in North America and Japan. Consequently, the cause of tree damage cannot be attributed to bears marking their territory. Bears damage trees by peeling the bark off the stem. The stem and the inner part (phloem) of the bark show teeth marks. The bark from the damaged trees is scattered around the trees. The brown bear almost exclusively damaged silver fir trees of larger breast diameters growing in uneven-aged stands (the diameter classes of damaged trees range from 22.5 to 77.5 cm, with the damage degree culminating at 42.5 cm). Distribution of the total number of trees, as well as the number of fir trees in the sample plots showed very high correlation with the theoretical distribution (Liocourt curve) typical of a beech-fir stand (R2=0.9629; p<0.0001; R2=0.93284; p<0.0001, respectively); however, in terms of breast diameter distribution, trees damaged by the brown bear show the typical Gaussian distribution (c2=4.93076; p =0.5572). The bear selected thicker fir trees in the sample plot (Kruskal-Wallis test c2=139.5987; p =0,001); in other words, trees with breast diameters of 57.5 cm have the highest preference index (proneness to damage). The analysis of fir bark chemical composition (Weende analysis) showed that the quantity of raw ash (minerals), proteins, NET, calcium and phosphorus in the fir bark was higher in the locality in which damage occurred more frequently. There are several theories dealing with this topic, of which the most plausible include space over-capacity, accessibility of animal food, increased lair density and stand structure. For this reason, the topic should be studied in more detail.